MOLECULAR DIVERSITY ANALYSIS OF FLOWER COLOUR VARIANTS OF BUTEA MONOSPERMA (LAM.) TAUB. USING INTER SIMPLE SEQUENCE REPEATS - KANDASAMY, THAMILARASI; KUMARI, KANCHAN; KAPRAKKADEN, ANEES; D. LOHOT , VAIBHAV; J. GHOSH (The Bioscan, 2013)
Butea monosperma is the most important host tree for the rangeeni strain of lac insect, Kerria lacca, exploited commercially in India for lac cultivation. Six flower colour variants of B. monosperma viz., scarlet, yellow, golden yellow, chrome yellow, white and mustard colour were collected from different regions of Jharkhand. Inter Simple Sequence Repeat (ISSR) marker system was employed to investigate the genetic structure and diversity among these flower colour variants. Out of 45 ISSR primers, 12 were found to be informative generating 127 scorable bands. A maximum of 19 and a minimum of 7 scorable bands per primer were obtained. The resolving power of the primers ranged between 2 and 11.3. Average polymorphic band percentage for all the primers was 85%. The marker index ranged from 2.9 to 15.85. The estimated Jaccard similarity coefficient ranged from 0.35 to 0.52. The clustering analysis using Jaccard’s coefficient showed 2 clusters; first - yellow and golden yellow and second - mustard, scarlet, chrome yellow and white flower colour variants.